Regional Perspectives on Policy Evaluation - Percoco, Marco; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The evaluation of public policies is of paramount importance for modern policy making, especially in a period of severe budget constraints. The literature has proposed several methods to deal with the issue of causality and counterfactual evaluation in a variety of contexts, with an increasing attention to the local dimension. The book aims to present the state-of-the-art of evaluation techniques with a special focus on the consideration of geographical and spatial effects into existing methodologies (such as propensity score matching, regression discontinuity, difference-in-difference). Furthermore, the volume highlights how strict the identification conditions for models with spatial effects are and proposes instrumental variables as a technique able to circumvent the issue. Finally, some insights into the emerging literature on ex ante evaluation are offered with respect to EU Cohesion Policy.
Introduction -- Regression Discontinuity Design: When Series Interrupt -- Propensity Score Matching: When Units Meet -- Difference-in-Differences: When Time and Space Matter -- A Synthetic Control Approach to Evaluate Local Policies -- Methods for Ex Ante Evaluation.
Keywords: Economics; Geography; Economic policy; Europe -- Economic policy; Regional economics; Economics/Management Science; Regional/Spatial Science; Economic Policy; European Integration; Economic Geography